Avaliação de um simulador de mama para estudo da interferência do implante de silicone na visualização de achados mamográficos - Valença, João Vinícius Batista (2012)
The establishment of specific equipment with the only purpose of evaluation the breast tissue has brought important improvement in mammary cancer detection. Presenting a huge variety in its characteristics, the female breasts varies in density and also in thickness, the mammographer it is useful in many occasions, including breast with artificial implants. The goal of this work is evaluate, using as main parameters the effective atomic number (Zef) and the total mass attenuation coefficient (ì/ñ), the mixture between paraffin gel and acrylic powder as breast simulator, as well as use the best proportion of these materials to analyze the interference of the silicone implant in images. Showing a rapid manufacture procedure, and requiring low cost materials, the simulator built with the proportion Paraffin+10%acrylic , which represents the addition of 10% of acrylic in the value of the paraffin, was the one that simulated best the mammary glands. The adipose tissue, which the proximity was greater, the percentage differences obtained to ì/ñ were approximately 32,9% for 10keV, 28,5% for 15 keV, 20,2% for 20 KeV, 11,1% for 30 keV e 5,4% for 40 keV. The evaluation in terms of implant interference showed that the scattered radiation produced by it has an approximated range of 5 mm to the built simulator which was introduced a 105 mL implant. Exposures with different compressions characteristics also were made, which was clear the influence in the image with quality and less time exposure